Hubungan Mutu Pelayanan Kesehatan Dasar Dengan Loyalitas Pasien Rawat Jalan Di UPTD Puskesmas Medang : Relationship Of The Quality Of Basic Health Services With The Loyalty Of Outpatient Patients At UPTD Puskesmas Medang - Siska Anggun; Harjanti; Trismianto Asmo Sutrisno (Indonesian Journal of Health Information Management, 2026)
The health development carried out at Puskesmas aim to create a healthy working area, with society who have healthy behavior and they able to access quality health services, live in a healthy environment and have an optimal level of health. Quality service results patients loyality to the Puskesmas. Preliminary studies show that patient visits in the last three months of 2023 have decreased. Preliminary studies show that 40% of patients said the services was good, the officers were friendly, and the officers were kind, while 60% of patients said the registration officers were not friendly, the service was very disappointing, the officers were incompetent, and the communication of officers was less effective.This study aim to determine the relationship between the quality of basic health services with the loyalty of outpatients from the aspects of physical evidence (tangible), reliability, responsiveness, assurance and empathy at the UPTD Puskesmas Medang. This study used a cross sectional design with a total population of 2107 and a sample of 95 people who were determined using a simple random sampling technique by giving questionnaires to outpatients according to the inclusion criteria at the UPTD Puskesmas Medang. Based on the results of the relationship analysis using the chi-square test (p<0.05), it shows that there is a relationship between service quality (p=0.000) and patient loyalty at the UPTD Puskesmas Medang. Puskesmas should improve the quality of service from the tangible aspect about the Puskesmas’s facilities and infrastructure and the responsiveness aspect about related to the soft skills of officers.